Enantioselective synthesis of crotyl geminal bis(silane) and its usage for asymmetric Sakurai allylation of acetals. Issue 26 (29th June 2017) - Chu, Yang; Pu, Qiang; Tang, Zhixing; Gao, Lu; Song, Zhenlei
Abstract: Enantioselective synthesis of crotyl geminal bis(silane)4 has been developed by an asymmetric [1, 5]-hydride shift of allylic hydrazine. SnCl4 -promoted Sakurai allylation of ( R )-4 with acetals leads to chemoselective desilylation of SiMe3, generating E - syn -( S, R )-5 in good yields with high E/Z -, diastereo- and enantioselectivity. Graphical abstract: